Magnetic and dielectric properties of nanophase manganese-substituted lithium ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Jadhav, S. D.; Mulla, Imtiaz S.; Jadhav, K. M.; Chougule, B. K. (Journal of Magnetism and Magnetic Materials, 2009)
Nanocrystalline manganese-substituted lithium ferrites viz. Li0.5Fe2.5-xMnxO4 (2.5 <= x >= 0) were prepared by sol-gel autocombustion method. X-ray diffraction analysis confirmed that as the concentration of manganese increases the cubic phase changes to the tetragonal phase. The variation of saturation magnetization was studied as a function of manganese content. All the compositions indicate that they are ferrimagnetic in nature. The dielectric constant, dielectric loss tangent and ac conductivity of all samples were measured at room temperature as a function of frequency. These parameters decrease with increase in frequency for all of the samples. The substitution of manganese plays an important role in changing the structural and magnetic properties of these ferrites. The compositional variation of dielectric constant and d.c. resistivity shows an inverse trend of variation with each other. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Ferrite; Magnetization; X-ray diffraction

Magnetic, dielectric and complex impedance spectroscopic studies of nanocrystalline Cr substituted Li-ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Garadkar, K. M.; Sasikala, R.; Tripathi, A. K.; Mulla, Imtiaz S. (Journal of Magnetism and Magnetic Materials, 2010)
Nanocrystalline Li0.5Fe2.5-xCrxO4 (2.5 <= x >= 0) ferrites were prepared by a sol-gel autocombustion route. X-ray diffraction was employed to confirm the cubic spinel phase formation of the ferrites. The lattice parameter decreases with increase in Cr content. The saturation magnetization, coercivity and remanance were studied as a function of Cr content. The dielectric constant and dielectric loss were measured as a function of frequency in the frequency range 20 Hz-1 MHz. Frequency dependence of dielectric constant shows dielectric dispersion due to the Maxwell-Wagner type of interfacial polarization. In order to understand the conduction mechanism, complex impedance measurements were carried out. The substitution of chromium plays an important role in changing the dielectric and magnetic properties of lithium ferrites. (C) 2010 Published by Elsevier B.V.
Keywords: Complex impedance; dielectric response; Ferrites; Magnetic hysteresis; Sol-gel synthesis; X-ray diffraction